The Effect of Political Risk on Foreign Direct Investment: The Case of Algeria - Midoun SISSANI; Zairi BELKACEM (Hyperion Economic Journal, 2014)
Both political risk and financial risk represent a great loss of profitable opportunities in the host countries and a serious threat on the attractiveness of foreign direct investments (FDI)in almost all developing countries among them Algeria . Methods & results: This paper attempts to study the significant relationship between political risk, financial risk and their effects on Foreign Direct Investment (FDI) in Algeria during 1990 to 2012.In fact, our analysis revealed that political has a negative relationship with (FDI) however financial risk was strong.